항공기 조류충돌 예방을 위한 조종사 비행중 결심 역량 증진방안 연구 - 이장룡; 허강; Lee, Jang Ryong; Huh, Gang (한국항공운항학회지, 2019)
While various efforts are being made to ensure aviation safety, air accident rate induced by pilot human factors is still high worldwide. In particular, among pilot human factors, it would be the most important issue for pilots to anticipate and recognize flight environmental factors beyond their control and to make a positive decision making(ADM). In the Republic of Korea Air Force(ROKAF), there were many dizzying experiences induced by bird strike incidents and developed into dangerous moments such as damage to the aircraft and pilots' increased mental stress. It is a matter of serious concern in terms of safety management and human factors to dismiss bird strike incidents as inevitable misfortune due to environmental factors. In 2018, the ROKAF Aviation Safety Agency(ASA) conducted an experimental study to enhance pilots' ADM competence that can anticipate and avoid a bird strike. As the way of the study, 'Bird Strike Preventing Information' had been written and distributed every week by the ASA to flight units in the ROKAF during the period of the study. Through enhanced pilots' perceptual ADM competence, there was a noticeable number of reduction in bird strike incident compared to previous years of the experimental study.